APPLICATION OF ENERGY EFFICIENCY EVALUATION METHODS FOR COMMERCIAL BUILDINGS IN AGRIBUSINESS - Filho, Luís R. A. Gabriel [UNESP]; Rodrigues, Cristhian A. [UNESP]; Halmeman, Maria C. R.; de Oliveira, Sandra C. [UNESP] (FapUNIFESP (SciELO), 2023)
Agribusiness and commerce are two major sectors that consume electricity. Agribusiness can generate energy but not enough to meet its needs. Thus, energy efficiency is fundamental for the sector’s sustainability. This study aimed to apply PROCEL energy evaluation methods in a Brazilian agribusiness company, specifically in the meat retail sector, located in the Alta Paulista region. This research has a quantitative approach, and PROCEL’s RTQ-C manual, bibliographical research on the energy issue, and the functioning of the company’s environment were used. The commercial establishment received the B classification index, which can be considered good but has several points of improvement, mainly on air conditioning, which provides better energy efficiency to the company. Therefore, the company can obtain economic and environmental returns by improving such areas, and the present research serves as a basis for evaluating energy efficiency in other companies in the same sector.
Keywords: buildings; electrical energy; retail sector; RTQ-C